2020
DOI: 10.1002/jbm4.10358
|View full text |Cite
|
Sign up to set email alerts
|

How Does Obesity Influence the Risk of Vertebral Fracture? Findings From the UK Biobank Participants

Abstract: Obesity and osteoporotic-related fractures are two common public health problems, although it is unclear how obesity affects the risk of vertebral fractures. The purpose of this study was to examine the association between different measures of obesity and the risk of vertebral fracture, and to establish the various clinical factors that can predict such risk. We analyzed data obtained from 502,543 participants in the UK Biobank (229,138 men and 273,405 women), aged 40 to 69 years. Imaging information was avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
(73 reference statements)
1
20
0
Order By: Relevance
“…Fifty-four studies were also discarded because the full-text was not available. The full-text of the remaining 487 reports was assessed for eligibility: 353 studies were excluded, leaving 134 for inclusion in the systematic review [ 20 22 , 25 , 52 181 ]. All included studies were in English or French.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-four studies were also discarded because the full-text was not available. The full-text of the remaining 487 reports was assessed for eligibility: 353 studies were excluded, leaving 134 for inclusion in the systematic review [ 20 22 , 25 , 52 181 ]. All included studies were in English or French.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also reported lower bone turnover in obesity, with a predominance of reduced bone formation over bone resorption [ 23 , 24 ]. Besides, some studies also used obesity criteria other than BMI to assess the association between obesity and bone fragility [ 25 27 ]. Furthermore, coexistence of obesity with type 2 diabetes, which has also been associated with an increased risk of fracture [ 19 ], deteriorated bone microarchitecture (e.g., increased cortical porosity) and altered bone turnover [ 19 , 28 ], may further impair bone health in individuals with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we can predict that as weight increases, spinal bone density increases, and the fracture rate decreases. Another study showed that high BMI and waist circumference in women were associated with a decrease in bone density due to increase in fat mass; however, whether these factors affect the lumbar spine fracture rate needs further study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that high BMI and waist circumference in women were associated with a decrease in bone density due to increase in fat mass; however, whether these factors affect the lumbar spine fracture rate needs further study. (25) Recently, it was reported that obesity is related to the site of fragility fractures. One study found that obesity led to lower risk of lumbar and femur fractures (17) ; however, another study showed that obesity increased the non-vertebral fracture rate.…”
Section: Discussionmentioning
confidence: 99%